Antipsicotici di nuova generazione: i loro effetti avversi non ancora segnalati - Romano, Francesca; Marzano, Lorenzo; Consolazione, Michol (Il sogno della farfalla, 2008)
This article takes into examination studies relative to the adverse effects of the new generation antipsychotics as indicated by the literature but not yet completely reported in the technical information of the pharmaceuticals. The specific correlation between the use of such drugs and an increase in the principle risk factors concerning cardiovascular diseases, among which weight gain, insulinic resistance, diabetes mellitus, cardiotoxicity and hyperprolactinemia is highlighted. In the face of the enthusiastic reception given to the introduction of the anti-psychotics, the necessity emerges for a major assessment of the adverse effects important for the health of the patients.